A postbiotic fermented oat gruel may have a beneficial effect on the colonic mucosal barrier in patients with irritable bowel syndrome - Bednarska, Olga; Biskou, Olga; Israelsen, Hans; Winberg, Martin E.; Walter, Susanna; Keita, Åsa V. (Frontiers in Nutrition, 2022)
Background: Impaired intestinal permeability and microbial dysbiosis are important pathophysiological mechanisms underlying irritable bowel syndrome (IBS). ReFerm®, also called Profermin®, is a postbiotic product of oat gruel fermented with Lactobacillus plantarum 299v. In this study, we investigated whether ReFerm® has a beneficial effect on the intestinal epithelial barrier function in patients with IBS. Material and Methods: Thirty patients with moderate to severe IBS-diarrhoea (IBS-D) or IBS-mixed (IBS-M) were treated with enema containing ReFerm® or placebo. The patients underwent sigmoidoscopy with biopsies obtained from the distal colon at baseline and after 14 days of treatment with ReFerm® or placebo twice daily. The biopsies were mounted in Ussing chambers, and paracellular and transcellular permeabilities were measured for 120 min. In addition, the effects of ReFerm®/placebo on the epithelial barrier were investigated in vitro using Caco-2 cells. Results: ReFerm® reduced paracellular permeability (p < 0.05) and increased transepithelial resistance (TER) over time (p < 0.01), whereas the placebo had no significant effect. In ReFerm®-treated Caco-2 cells, paracellular and transcellular permeabilities were decreased compared to the control and placebo groups. TER was increased in Caco-2 ReFerm®-treated cells, and normalised TER was increased in ReFerm®-treated Caco-2 cells compared to control and placebo-treated cells. Conclusions: ReFerm® significantly reduced paracellular permeability and improved TER in colonic biopsies collected from patients with IBS and in a Caco-2 cell model. Our results offer new insights into the potential benefits of ReFerm® in IBS management. Further studies are needed to identify the molecular mechanisms underlying the barrier-protective properties of ReFerm®.